Clinical comparison of low-volume agents (oral sulfate solution and sodium picosulfate with magnesium citrate) for bowel preparation: the EASE study - Jeeyeon Kim; Hyun Gun Kim; Kyeong Ok Kim; Hyung Wook Kim; Jongha Park; Jeong-Sik Byeon; Sung-Wook Hwang; Hyun Deok Shin; Jeong Eun Shin; Hyo-Joon Yang; Hyun Seok Lee; Yunho Jung; et al. (Intestinal Research, 2019)
Background/Aims This study compared the efficacy, compliance, and safety of bowel preparation between sodium picosulfate with magnesium citrate (SPMC) and oral sulfate solution (OSS). Methods A prospective randomized multicenter study was performed. Split preparation methods were performed in both groups; the SPMC group, 2 sachets on the day before, and 1 sachet on the day of the procedure, the OSS group, half of the OSS with 1 L of water on both the day before and the day of the procedure. The adenoma detection rate (ADR), adequacy of bowel preparation using the Boston Bowel Preparation Scale (BBPS) score, patient satisfaction on a visual analog scale (VAS), and safety were compared between the 2 groups. Results This study analyzed 229 patients (121 in the SPMC group and 108 in the OSS group). ADR showed no differences between 2 groups (51.7% vs. 41.7%, P>0.05). The mean total BBPS score (7.95 vs. 8.11, P>0.05) and adequate bowel preparation rate (94.9% vs. 96.3%, P>0.05) were similar between the 2 groups. The mean VAS score for taste (7.62 vs. 6.87, P=0.006) was significantly higher in the SPMC group than in the OSS group. There were no significant differences in any other safety variables between the 2 groups except nausea symptom (36.1% vs. 20.3%, P=0.008). Conclusions Bowel preparation for colonoscopy using low volume OSS and SPMC yielded similar ADRs and levels of efficacy. SPMC had higher levels of satisfaction for taste and feeling than did OSS.